Efficacy of platelet-rich plasma for the treatment of interstitial supraspinatus lesions: A randomized, double-blinded, controlled trial: PRP for Interstitial Supraspinatus Lesions. Issue 5 (31st May 2019) - Schwitzguebel, Adrien J; Kolo, Frank C.; Tirefort, Jérome; Kourhani, Abed; Nowak, Alexandra; Gremeaux, Vincent; Saffarini, Mo; Lädermann, Alexandre
Objectives: To determine whether platelet rich plasma (PRP) infiltrations are superior to saline solution infiltrations (placebo), when injected under ultrasound guidance within isolated interstitial supraspinatus tears, at improving healing, pain and function. Methods: In this single-centre, double-blinded, randomized control trial, 84 adults, diagnosed with symptomatic isolated interstitial tears of the supraspinatus, confirmed by their magnetic resonance arthrography (MRA) were randomized to PRP or saline injections. Each patient received 2 injections at 1 month interval. The primary outcome was the change in lesion volume calculated on MRA, at 7months. The secondary outcomes were improvements in shoulder pain and clinical scores at >12months. Results: Pre-operative patient characteristics did not differ between the two groups. At 7 months, there were no significant differences between the PRP and control groups in terms of decrease in lesion size (-0.3±23.6mm 3 vs -8.1±84.7mm 3 ; p=0.18), reduction of pain on Visual Analogic Scale (2.3±3.0 vs 2±3.0; p=0.59), improvement of Single Assessment Numerical Evaluation (16.7±20 vs 14.2±29.0; p=0.65), Constant score (8.6±13.0 vs 10.6±19.0; p=0.60), or American Shoulder and Elbow Surgeons (19.5±20.0 vs 21.9±28.0; p=0.67) scores. Adverse effects (frozen shoulders and extension of lesion to bursal or articular surface) were significantly more frequent in the PRP group compared to the control group (54% vs 26%, p=0.02). Conclusion: PRP injections within interstitial supraspinatus tears did not improve tendon healing nor clinical scores compared to saline injections, and were associated with more adverse events. These findings confirm that PRP is of little benefit in the treatment of rotator cuff tears.